The Heterogeneous Impacts of Human Capital on Green Total Factor Productivity: Regional Diversity Perspective - Xiao, Hang; You, Jialu (Frontiers in Environmental Science, 2021)
Human capital improves the efficiency of GTFP has been established in research fields, but the heterogeneous effects of human capital on GTFP and its sustainable mechanisms are unclear. This study aims to examine the effects of human capital accumulation, education fiscal, and innovation on GTFP efficiency under diversity between spatial and temporal. Employing panel data from 30 provinces from 2001 to 2018 in China, We analyzed the dynamic and static efficiency of GTFP at different regions by three-stage DEA. We explored the heterogeneous effects of human capital on GTFP through Tobit regression. Results show that the average value of GTFP efficiency is inverted U-shape and having a significant geography difference. Then, human capital accumulation and education fiscal have positive effects on the GTFP efficiency; however, innovation negatively affects GTFP efficiency. At the same time, marketization growth decreases human capital and education's positive influence on GTFP efficiency. However, it was not seen on the innovation—the implication of these results concerning the human capital heterogeneous effects of GTFP efficiency in different geography. Establishing a fair and transparent system is an available choice to reduce the endowments gap and effectively promote GTFP efficiency in developing countries.